2020
DOI: 10.1136/bmjopen-2019-030503
|View full text |Cite
|
Sign up to set email alerts
|

Eversion technique versus conventional endarterectomy with patch angioplasty in carotid surgery: protocol for a systematic review with meta-analyses and trial sequential analysis of randomised clinical trials

Abstract: IntroductionTraditional carotid endarterectomy is considered to be the standard technique for prevention of a new stroke in patients with a symptomatic carotid stenosis. Use of patch angioplasty to restore the arterial wall after longitudinal endarterectomy is, to date, not unequivocally proven to be superior to eversion technique. A systematic review is needed for evaluation of benefits and harms of the eversion technique versus the traditional endarterectomy with patch angioplasty in patients with symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
0
5
0
1
Order By: Relevance
“…The main advantage of the ECEA is that there is no need for a patch that minimizes the operative time and risk of postoperative infection. However, the difficulty of inserting the shunt before removing the plaque and the high rates of postoperative hypertension due to transecting the carotid sinus nerve branches and loss of baroreceptors limit its use [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of the ECEA is that there is no need for a patch that minimizes the operative time and risk of postoperative infection. However, the difficulty of inserting the shunt before removing the plaque and the high rates of postoperative hypertension due to transecting the carotid sinus nerve branches and loss of baroreceptors limit its use [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that both eversion CEA and CCEA operations were safety methods with very rates low complication. Therefore, it is important that carotid surgery is performed by experienced surgeons with sufficient experience of the procedure, as emphasized in the guidelines (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…This review was conducted according to our published protocol [ 33 ] and was registered at PROSPERO ( https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42019119361 ) [ 34 ], following the recommendations of the ‘Cochrane Handbook for Systematic Reviews of interventions’ [ 30 ] and is reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses ( PRISMA ) statement ( www.prisma-statement.org ) [ 35 ] and Assessing the methodological quality of systematic reviews (AMSTAR) guidelines [ 36 ]. According to the AMSTAR 2 Checklist, (enclosed as supplementary material) this review may be considered as a high-quality review.…”
Section: Methodsmentioning
confidence: 99%